Birgittas Vårdcentral - Elisson, Alexandra; Waschek, Mathias; Müller-Zitzke, Paul (My University, 2023)
The site proposed by the community of Vadstena for a new primary care center is characterized by historical aspects such as the long tradition of healthcare facilities, topographical by several areas with different characteristics, sociological by an aging community and architecturally through clear vernacular buildings and features, present to this day. By adding a a timber top-up and extension to the existing building we believe to have accomplished a sensible and simultaneously ecologic, economic and social worthwhile transformation. Vernacular elements such as the existing brick facades, roof type and general proportions are emphasized by clearly contrasting with the light post & beam addition. The addition draws inspiration from its surroundings and interprets it for a new expression. Apart from physical changes we propose a holistic approach to healthcare that works health promoting rather than treatment focused. Apart from ecologic and economic aspects, we also included the social standpoint. By empowering the citizens to take care of all facets of their health, the facility will aid in taking strain off of the healthcare system and facilitate the change towards a more sustainable and efficient health promoting system.